2005
DOI: 10.1007/bf03337714
|View full text |Cite
|
Sign up to set email alerts
|

Visual assessment of medial temporal atrophy on MR films in Alzheimer’s disease: comparison with volumetry

Abstract: The visual rating scale of MTA, easily applicable in clinical practice, shows good agreement with more demanding quantitative methods, and can discriminate AD patients from controls with good accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
2
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 11 publications
7
47
2
2
Order By: Relevance
“…Furthermore, the assessments of WMH and of MTA are based on visual rating. Although the rating scale used in the study has shown a good sensitivity in the detection of WMHs [27] , and MTL [51,30] , volumetric measurement of WMHs and medial temporal structures with quantitative advanced tools could be useful to confirm the present findings. Lastly, longitudinal data are available for a small fraction of patients.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, the assessments of WMH and of MTA are based on visual rating. Although the rating scale used in the study has shown a good sensitivity in the detection of WMHs [27] , and MTL [51,30] , volumetric measurement of WMHs and medial temporal structures with quantitative advanced tools could be useful to confirm the present findings. Lastly, longitudinal data are available for a small fraction of patients.…”
Section: Discussionsupporting
confidence: 63%
“…Visual scales may not be as sensitive as structural volumetry, but they are cost-effective, usable in clinical practice, and have been proved to reach good reliability and correspondence to volumetric measurements. 38,39 In our evaluations, we separated subcortical and cortical atrophy, but were not able to evaluate specific cortical regions. Another disadvantage of the study is that brain atrophy was only evaluated at baseline and measures of progression were only available for lacunes and WML for a subgroup of the sample.…”
Section: Figure 2 Combined Effects Of White Matter Lesions (Wml) and mentioning
confidence: 99%
“…Visual rating such as medial temporal atrophy ratings scales [31] has been shown to distinguish clinically diagnosed AD patients from controls with a sensitivity of approximately 85% for a specificity of 80% [32]. Width of temporal lobe on MRI has been shown to have a sensitivity of 86% and a specificity of 93% when discriminating AD subjects from controls [33].…”
Section: Discussionmentioning
confidence: 99%